The Influence of Work Motivation, Employee Placement, and Competency Development on Achieving Production Target In the Blow Moulding Industry - Herman Sjahruddin; Pandu Adi Cakranegara; Rezky Nurbakti; Uli Wildan Nuryanto; Joni Prihatin (PT Mattawang Mediatama Solution, 2022)
The purpose of this study was to analyze the influence of work motivation, employee placement and competency development on the achievement of production targets. The method used in this study is the associative method using quantitative analysis. From the research that has been done, it is obtained that the value of t count > t table so that work motivation, employee placement and employee competency development have a positive and significant impact on employee performance in achieving the production targets that have been set. The R-square value obtained is 0.558 which states that the variables of work motivation, employee placement and competency development affect the achievement of production targets by 55.80% and the remaining 44.20% is influenced by other variables.